Key Trends in Implementing the Fund's Transparency Policy. (Policy Papers; Policy Paper ;, 2018)
The IMF's transparency policy allows for the deletion of market-sensitive information and premature disclosure of the authorities' policy intentions in published staff reports and other documents. The Report prepared by IMF staff and completed on December 6, 2017 has been released. The staff report was issued to the Executive Board for information. The report was prepared by IMF staff. The views expressed in this paper are those of the IMF staff and do not necessarily represent the views of the IMF's Executive Board.